Evaluation of Anomalous Coronary Arteries from the Pulmonary Artery - Guzeltas,Alper (2017)
Abstract Objective: This study evaluated clinical and diagnostic findings, treatment methods, and follow-up of cases of anomalous coronary arteries from the pulmonary artery. Methods: The study included all cases diagnosed with anomalous coronary arteries from the pulmonary artery between January 2012 and January 2016. Data from patients’ demographic characteristics, electrocardiography, echocardiography, angiographic findings, operation, intensive care unit stay, and follow-up were evaluated. Results: The study included 12 patients (8 male, 4 female), 10 with anomalous left coronary artery from the pulmonary artery (ALCAPA) and 2 with anomalous right coronary artery from the pulmonary artery (ARCAPA). Median age at diagnosis was 4 months (range, 1 month - 10 years old) and median weight was 5.5 kg (range, 3-30 kg). The most common complaints were murmur (n=7) and respiratory distress (n=5). In 4 cases, the initial diagnosis was dilated cardiomyopathy. Electrocardiographs were pathologic in all cases. Echocardiographic examination revealed medium to severe mitral valve regurgitation in 4 cases and reduced (< 40%) ejection fraction in 6 patients. Of the 12 patients, 8 underwent direct implantation of the left coronary artery into the aorta, 2 underwent implantation of the right coronary artery into the aorta, and the remaining 2 underwent a Takeuchi procedure. There were no early mortalities. Median hospital stay was 20 days (range, 5-35 days). Median follow-up duration was 18 months (range, 5-36 months), and no cases required further surgery during follow-up. Conclusions: Anomalous coronary arteries from the pulmonary artery can be successfully repaired providing there is early diagnosis and effective, appropriate intensive care unit follow-up. Therefore, coronary artery origins should be evaluated carefully, especially in cases with dilated cardiomyopathies.